Peran Guru PAI Dalam Membentuk Karakter Islami Siswa MAS Al-Wasliyah Tembung - Fitri Alkomariah Siagian; Nur Fauziah Harahap; Muliadi Muliadi; Widia Rahayu; Fiona Shopie Audrie; Arlina Arlina (EduInovasi: Journal of Basic Educational Studies, 2023)
The role of Islamic religious education (PAI) teachers cannot be overstated in shaping the identity of Muslim students in formal education settings such as schools and mosques; this article, in particular, draws attention to the contributions of Guru Aqidah Akhlak. Because of the role of the Aqidah Akhlak teacher as a role model, role model, and idol for his students, it is hoped that they can be formed into Muslims through pedagogical techniques which are usually in the form of lectures and reprimands. The purpose of this study was to find out (1) how much influence the Aqidah Akhlak curriculum had in shaping the Islamic identity of MAS Al-Wasliyah Tembung students. (2) Analyze the supporting and inhibiting factors encountered in implementing Islamic reform. 3. Study the responses of MAS Al-Wasliyah Tembung students. How big is the change before and after MAS Al-Wasliyah Tembung students shape their Islamic character profile? This study uses a quantitative descriptive research design. Data collection through interviews, observation, and written notes. Next, a descriptive quantitative analysis was carried out by providing the relevant data set. The results showed that the role of Islamic religious education teachers, especially teachers of Islamic religious beliefs in shaping the Islamic character of MAS Al Wasliyah students, was as a guide, educator, leader, and motivator. . Students at MAS Al-Wasliyah Tembung are expected to develop a peaceful, virtuous character by participating enthusiastically in religious education lessons — classes which usually involve reciting and reciting the Koran, as well as discussing its meaning with a qualified teacher, or 'Gurus Tahfiz. . Keywords: The Role of Islamic Education Teachers, Islamic Character.